Keluarga sebagai Basis Penguatan Karakter Dasar Anak - Fajar Indarsih (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2023)
The character education of children in the family should not be regarded as simple and unimportant. Some families seem indifferent to children's character education is indeed a serious challenge in modern society. Character education is an important part of children's development which includes aspects of morals, ethics, attitudes, and positive values that will help them become good and responsible citizens in society. The purpose of this study is to describe the role of the family in strengthening the basic character of children. The research method used is qualitative, with the type of literature research. The method of obtaining data uses documentation, namely books, articles, and reference sources related to the title. The result of the study is that the family has a very important role in shaping the basic character of children. They are the first agents of character formation of children from an early age. Daily interactions with parents, siblings, and other family members form the foundation of a child's character, such as values, attitudes, and good behavior.